The Model of Successful Interorganizational Collaboration in Digital Inclusion Field - Kulikauskienė, Kristina; Šaparnienė, Diana (Social Welfare: Interdisciplinary Approach, 2026)
The aim of this article is to reveal the critical success factors of interorganizational collaboration in increasing digital inclusion in public libraries and to create a theoretical model of successful interorganizational collaboration. The theoretical significance of the study lies in integrating and extending existing knowledge on interorganizational collaboration by synthesizing relevant literature and applying the quadruple helix model to the field of digital inclusion. By using the constructivist grounded theory methodology, 21 semi-structured interviews were conducted with representatives of public libraries, higher education institutions, local government bodies, NGOs, businesses, and digital inclusion experts. Based on the formed grounded theory, this model reveals the critical success factors of interorganizational collaboration: mutuality, the integration of contractual and relational governance mechanisms, and collaborative capability, which were identified as having the greatest influence on the criteria for the success of interorganizational collaboration: the achievement of collaboration goals, ensuring the sustainability of the results achieved, and partner satisfaction with the collaboration process. The practical significance of the study lies in providing a structured framework and actionable insights for public libraries and their partners to design, manage, and sustain effective collaborative initiatives that promote digital inclusion at the community level and thus contribute to the well-being of society.